Triple quadrupole LC/MS method for the simultaneous quantitative measurement of cefiderocol and meropenem in serum. Issue 6 (19th January 2023) - Riezk, Alaa; Vasikasin, Vasin; Wilson, Richard C.; Rawson, Timothy M.; McLeod, James G.; Dhillon, Rishi; Duckers, Jamie; Cass, Anthony E. G.; Holmes, Alison H.
Abstract : LC/MS method for the simultaneous quantitative measurement of cefiderocol and meropenem in serum samples. Abstract : Background : therapeutic drug monitoring is a crucial aspect of the management of hospitalized patients. The correct dosage of antibiotics is imperative to ensure their adequate exposure specially in critically ill patients. The aim of this study is to establish and validate a robust and fast liquid chromatography-tandem mass spectrometry (LC/MS) method for the simultaneous quantification of two important antibiotics in critically ill patients, cefiderocol and meropenem in human plasma. Methods : sample clean-up was performed by protein precipitation using acetonitrile. Reverse phase chromatography was performed using triple quadrupole LC/MS. The mobile phase was consisted of 55% methanol in water +0.1% formic acid, with flow rate of 0.4 ml min −1 . Antibiotics stability was assessed at different temperatures. Serum protein binding was assessed using ultrafiltration devices. Results : chromatographic separation was achieved within 1.5 minutes for all analytes. Validation has demonstrated the method to be linear over the range 0.0025–50 mg L −1 for cefiderocol and 0.00028–50 mg L −1 for meropenem, with accuracy of 94–101% and highly sensitive, with LLOQ ≈ 0.02 mg L −1 and 0.003 mg L −1 for cefiderocol and meropenem, respectively. Both cefiderocol and meropenem showed a good stability at room temperature over 6 h, and at (4 °C) over 24 h. Cefiderocol and meropenem demonstrated a protein binding of 49–60% and 98%, respectively in human plasma. Conclusion : the developed method is simple, rapid, accurate and clinically applicable for the quantification of cefiderocol and meropenem.